(untitled) (Nexus International Journal of Science and Education, 2024)
This study unearthed the experiences, coping mechanisms used and educational insights learned by the teachers in teaching English to Grade eight students. A qualitative approach to research phenomenological from the Eight (8) Secondary School Teachers coming from the Island Garden City of Samal. Experiences in teaching English to Grade Eight students were observed: Need to use a variety of teaching strategies, address the diverse learning needs of students, assess students' language proficiency, and engage students who have different levels of motivation and interest. The coping mechanisms used in addressing the challenges were as follows: creating a positive relationship with the students, adopting a growth mindset, collaborating with colleagues, and using technology and multimedia resources. Finally, the educational insights learned from the experiences of the teachers are the importance of building relationships with students, the value of using a variety of teaching strategies, the importance of addressing the diverse learning needs of the students, and the benefits of ongoing professional development. These were fundamental to the success of teaching English to Grade Eight students. All these themes can contribute to a deeper understanding of the Grade Eight teachers' experiences and offer valuable perspectives on effective teaching practices, student preferences, and the impact of various factors on language learning outcomes. This study may also be published in any respectable research journal.